Las causas de la prostitución josefina: 1939-1949. Entre lo imaginario y el estigma - Marín Hernández, Juan José (1993)
An analysis of the causes behind prostitution in San José and its increase between 1939 and 1949, based on the criteria expressed by the authorities and by opinion makers.